2012
DOI: 10.1130/ges00807.1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Structural syntaxes, tectonic aneurysms, and fault-bounded fore-arc slivers are important tectonic elements of orogenic belts worldwide. In this study we used high-resolution topography, geodetic imaging, seismic, and geologic data to advance understanding of how these features evolved during accretion of the Yakutat Terrane to North America. Because glaciers extend over much of the orogen, the topography and dynamics of the glaciers were analyzed to infer the location and nature of faults and shear zones that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 84 publications
(191 reference statements)
1
17
0
3
Order By: Relevance
“…Their analysis of glacial fl ow in the upper Seward Glacier leads to their suggestion of a releasing bend along the strike-slip system that they use to explain the unusual, very young, low-temperature cooling ages recognized in this area by Enkelmann et al (2009). Bruhn et al (2012) also use glacial fl ow and ice surface morphology to evaluate active structure across the Bagley Ice Field valley, and conclude that the valley is underlain by a longlived, dextral-oblique structure that remains active. Their use of glacial valley morphologies and comparison of the geology across the Bagley Ice Field valley leads to a provocative interpretation of ~50 km of dextral slip along with several kilometers of south-side-up displacement across the buried structure.…”
Section: Themed Issue Contentsmentioning
confidence: 96%
See 2 more Smart Citations
“…Their analysis of glacial fl ow in the upper Seward Glacier leads to their suggestion of a releasing bend along the strike-slip system that they use to explain the unusual, very young, low-temperature cooling ages recognized in this area by Enkelmann et al (2009). Bruhn et al (2012) also use glacial fl ow and ice surface morphology to evaluate active structure across the Bagley Ice Field valley, and conclude that the valley is underlain by a longlived, dextral-oblique structure that remains active. Their use of glacial valley morphologies and comparison of the geology across the Bagley Ice Field valley leads to a provocative interpretation of ~50 km of dextral slip along with several kilometers of south-side-up displacement across the buried structure.…”
Section: Themed Issue Contentsmentioning
confidence: 96%
“…The third paper in this series of contributions on the geology of the St. Elias orogen, that of Bruhn et al (2012), uses a novel approach to examine the bedrock geology in this heavily glaciated orogen. The authors use remote sensing data of exposed bedrock and glacier surfaces that integrate several years of observation for ice fl ow.…”
Section: Themed Issue Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Some studies have proposed that a dextral shear zone in the Bagley Ice Valley ( Figure S4) accommodates part of the relative plate motion within the orogen. Bruhn et al [2012] suggested that a Bagley fault might connect the thrust faults around Mount St. Elias with faults in the Bering Glacier area. Based on surveys of a trilateration network at the western end of the ice valley, Savage and Lisowski [1988] found significant dextral shear of~8 mm/yr across the Bagley.…”
Section: Blocks and Fault Geometriesmentioning
confidence: 99%
“…Several studies [e.g., Lahr and Plafker, 1980;Perez and Jacob, 1980;Savage and Lisowski, 1988;Estabrook et al, 1992] suggested models for the basic regional tectonic framework or focused on segments of the orogen, but available data were sparse, and major questions remained about the distribution of relative motion and the location of active structures, the present-day deformation front between the Yakutat block and southern Alaska, how far the effects of the collision extended, and the large-scale geodynamics of the collision. Work done in the past decade in geology [e.g., Chapman et al, 2008Chapman et al, , 2012Bruhn et al, 2004Bruhn et al, , 2012Pavlis et al, 2012], thermochronology [e.g., Enkelmann et al, 2009;Berger et al, 2008], and geodynamic modeling [Koons et al, 2010] has shed new light on the structural framework and temporal evolution of the orogen, but detailed estimates of present-day motions were still missing.…”
Section: Introductionmentioning
confidence: 99%